2013
DOI: 10.1007/s00384-013-1729-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sclerotherapy with polidocanol foam in comparison with fluid sclerosant in the treatment of first-grade haemorrhoidal disease: a randomised, controlled, single-blind, multicentre trial

Abstract: In the therapy of first-grade haemorrhoidal disease, polidocanol 3 % foam is more effective and equally safe compared to liquid polidocanol. The results of this trial show that foam sclerotherapy is a new, innovative, effective and safe non-surgical treatment option for haemorrhoidal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 18 publications
2
62
4
2
Order By: Relevance
“…More than 10 years ago, we begun using polidocanol 2% foam, which results from the mixture of liquid with air, changing drug characteristics with more sclerosing capacity and adherence to the endothelium with the same safety profile, but there is only one import study of its use and only on first-grade hemorrhoidal disease [18,19]. We learned with vascular surgery that used it regularly.…”
Section: Introductionmentioning
confidence: 99%
“…More than 10 years ago, we begun using polidocanol 2% foam, which results from the mixture of liquid with air, changing drug characteristics with more sclerosing capacity and adherence to the endothelium with the same safety profile, but there is only one import study of its use and only on first-grade hemorrhoidal disease [18,19]. We learned with vascular surgery that used it regularly.…”
Section: Introductionmentioning
confidence: 99%
“…The only prospective study that sufficiently related about III and IV degrees revealed 70% of subjective moderate/excellent improvement. Patients submitted to IS have a relatively low occurrence of post-procedural pain: 36% in I degree is reported by Moser, 49% is reported by Takano (36,41). Bleeding is a very rare harm.…”
Section: Discussionmentioning
confidence: 89%
“…Patients submitted to IS have a relatively low occurrence of post-procedural pain: 36% in I degree is reported by Moser, 49% is reported by Takano (36,41).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations